The effect of media golf professionals’ image on instructor trust and customer satisfaction - Kim, Ga-Young; Kim, Youbin; Yang, Hye Jin; Bum, Chul-Ho; Choi, Chulhwan (Frontiers in Psychology, 2025)
Since media golf professionals are mainly encountered online rather than through face-to-face instruction, it is difficult to assess their competency and expertise as instructors. To this end, the study sought to assess instructors’ instructional competence through the construct of instructor image and examine its influence on instructor trust and customer satisfaction. The participants were 290 Korean adult amateur golfers (186 men and 104 women). A questionnaire was used to measure perceptions of instructor image, instructor trust, and customer satisfaction. Data were analyzed using descriptive statistics, validity and reliability tests, and multiple regression analysis. First, the instructor image of media golf professionals was found to have a partially positive effect on instructor trust. Among the subfactors of instructor image, attitude did not have a significant effect. Second, instructor image had a significantly positive effect on customer satisfaction; however, among its sub-factors, qualification did not have a significant impact. Third, instructor trust had a significantly positive effect on customer satisfaction. In conclusion, the findings of this study state that a positive instructor image of media-based golf professionals fosters trust and satisfaction, thereby promoting continued participation in exercises and sustained viewing intentions.